Occurrence and Risk Factors of Brucellosis in Commercial Cattle Farms from Selected Districts of the Eastern Coast Zone, Tanzania - James P. Warioba; Esron D. Karimuribo; Erick V. G. Komba; Mwemezi L. Kabululu; Godwin A. Minga; Hezron E. Nonga (Veterinary Medicine International)
Brucellosis is a disease of major socio-economic importance worldwide, particularly in low-income countries. This retrospective study aimed to estimate seroprevalence and risk factors associated with brucellosis in commercial cattle farms in the eastern coast zone of Tanzania (ECZT). A total of 1,052 serum samples collected from 20 commercial farms were subjected to rose bengal plate test (RBPT) and indirect enzyme-linked immunosorbent assay (i-ELISA). Descriptive analysis was employed to determine frequencies and proportions. To establish risk factors, a multivariate logistic regression analysis was carried out using a backward elimination procedure, following a univariate analysis, with 0.1 set as a cut-off point for the selection of putative risk factors. Agreement between RBPT and i-ELISA was determined using a Kappa coefficient (κ). The overall animal-level seroprevalence was 25.9% based on i-ELISA. Logistic regression analysis revealed that odds of infection were significantly higher in females (OR = 1.8, 95% CI: 1.2–2.5, p = 0.002) and in young animals than in adults (OR = 3.6, CI: 2.1–6.2, p < 0.001). In addition, odds of infection were higher during the wet season (OR = 3.4, CI: 3.2–5.2, p < 0.001), in cattle reared in rural farms (OR = 4.8, CI: 2.0–11.5, p < 0.001), in cattle reared in areas, not in contact with wildlife (OR = 2.9, CI: 1.4–2.3, p = 0.004), and in medium-sized farms (OR = 12.5, CI: 6.9–22.9, p < 0.001). These findings confirm that bovine brucellosis was prevalent among commercial cattle farms in the ECZT, posing a serious public health concern to the community living in these settings. The one health approach should be adopted for effective control of brucellosis.